Local Resources-Based Community Empowerment Model to Achieve Food Security in the Indonesian Border Community of North Sebatik - Nia Kurniasih; Sekar Inten Mulyani; Hendris Hendris (Jurnal Kawistara, 2023)
Many scholars now see border areas to have a srategic value. They are no longer seen as the backyard of a country but the front yard that must be seen well developed. Therefore border communities must be empowered to be independent from neighboring countries. These include efforts to increase these independence through community empowerment. Community empowerment can increase the independence and welfare of the community through increasing knowledge, attitudes/behaviors, skills, abilities, awareness, and utilization of resources. Through the process, it is expected that human resources capacity will increase in food security. How the efforts to empower border communities adopt local resources, instead of a top down approach, however needs forther exploration. This research aims to asses the effects of human and natural capitals in formulating local resources-based Community empowerment model in the sector of food security. This research was conducted in the North Sebatik district, Nunukan regency with 65 sample of farmers selected through simple random sampling techniques. Primary and secondary data were collected through field observations, direct interviews, questionnaire distribution, and information obtained from official government agencies. This research uses human capital, nature capital, and social capital as dependent variables, and community empowerment and food security as independent variables. The analysis method applied Partial Least Square (PLS) by using software WarpPLS 5.0. The results of the research showed that human capital must go through an empowerment process to increase human quality. Natural capital must also go through an empowerment process, as human quality without supported nature resources cannot improve capacity to achieve food security. Social capital must also go through an empowerment process. Community empowerment has an impact on food security, as it can manage existing resources to create and improve household income through locally-based agricultural activities to achieve food security.